Robust superhydrophilic polylactide (PLA) membranes with a TiO2 nano-particle inlaid surface for oil/water separation. Issue 14 (17th March 2017) - Xiong, Zhu; Lin, Haibo; Zhong, Yun; Qin, Yan; Li, Tiantian; Liu, Fu
Abstract : To overcome the surface instability of traditional polymeric membranes especially with superwetting behaviour, a robust superhydrophilic surface was fabricated with nano-TiO2 inlaid on a hierarchical polylactide (PLA) ultrafiltration membrane via a spin coating process. Abstract : To overcome the surface instability of traditional polymeric membranes especially with superwetting behaviour, a robust superhydrophilic surface was fabricated with nano-TiO2 inlaid on a hierarchical polylactide (PLA) ultrafiltration membrane via a spin coating process. Distinctly different from most previously reported nano-particle involved polymeric membranes, both the micro-/nano-architecture of the PLA membrane and the size matched nano-particle assembly constructed the robust superhydrophilic interface mimicking coral tentacle predatory behavior. The rigid surface based on the flexible polymeric membrane with the hierarchical architecture showed robust superhydrophilicity and underwater superoleophobicity even after long-term water washing treatment, which was also verified by the morphology, contact angle, XPS and adhesive force in contrast to smooth membranes. The as-prepared PLA membrane showed excellent separation performance for varieties of oil/water mixtures with a robustly high permeate flux (above 950 L m −2 h −1 under 0.1 MPa) and oil rejection (above 99%) even after 10 cycles of operation. Besides, the superhydrophilic PLA membrane exhibited outstanding anti-protein fouling properties. The PLA membrane showed relatively high BSA and ink rejection as well as water flux recovery and continuous separation stability due to rigid interface strengthening effects. The unique interface combination strategy between functional nanoparticles and polymeric membranes provided a window of opportunity for constructing robust polymeric membranes for advanced applications e.g. oil/water separation, ion exchange, in membrane catalytic reactors etc.